Nutritional support and health care of orphan puppies or kittens during the first weeks of life - GOULETSOU (Π. ΓΚΟΥΛΕΤΣΟΥ) P.; FTHENAKIS (Γ. Χ. ΦΘΕΝΑΚΗΣ) G. C.; GALATOS (Α.Δ. ΓΑΛΑΤΟΣ) A. D. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this paper, actions and measures necessary for the nutritional support and health care of orphan puppies or kittens during the first weeks of life, are reviewed. Special reference is made to measures taken in order to provide ideal environmental conditions and proper nutrition, and to support urination, defecation and cleanliness of the newborn.